REFORMASI SYARI’AH DAN WACANA HAK ASASI MANUSIA (Studi Pemikiran Hukum Abdullah An-Na’m) - Jamhari, Jamhari (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: Abdullah An-Na'im is the figure of the modernthinker; his work is a good starting point of radical Islammodernist and fundamentalist position that both of themdominate contemporary thinking in the Islamic world.According to Shari'ah are no longer relevant and no longeradequate for the needs of modern society, it has led to seriousproblems when dealing with human rights standards. An-Na'imtransformed basic understandings of traditional Islamic law. Interms of Shari'ah, An-Na'im advocated a new system of Islamiclaw which is believed to provide a thorough foundation more inline with Islamic life in the contemporary world. This articlewill explore formulation in the face of political structures, socialorder, criminal law, international law and human rights.ملخص: عبد لله النعیم ھو الرقم المفكر المعاصر؛ عملھ ھو نقطة انطلاق جیدة لالحداثیة الإسلام المتطرفة و الموقف الأصولي أن كلا منھم تھیمن على التفكیرالمعاصر في العالم الإسلامي . وفقا ل أحكام الشریعة الإسلامیة لم تعد مناسبة والتي لمتعد كافیة لتلبیة احتیاجات المجتمع الحدیث، وقد أدى ذلك إلى مشاكل خطیرة عندالتعامل مع معاییر حقوق الإنسان. النعیم تتحول التفاھمات الأساسیة للقانون الإسلاميالتقلیدي. من ناحیة الشریعة الإسلامیة، دعا النعیم نظام جدید للشریعة الإسلامیة التيیعتقد أنھا توفر أساسا شاملا أكثر انسجاما مع الحیاة الإسلامیة في العالم المعاصر.ھذه المادة سوف تستكشف صیاغة في مواجھة البنى السیاسیة والنظام الاجتماعي،والقانون الجنائي والقانون الدولي و حقوق الإنسان.Kata Kunci : Reformasi Syariah, Abdullah An-Na’im